Effect of seed priming on maize (Zea mays L.) seedling emergence under different sowing dates (Bangladesh Journal of Agricultural Research, 2015)
The experiment was carried out at the research field of Regional Agricultural Research Station, Jessore during 2009-10 and 2010-2011 to find out the effect of priming and ambient temperatures due to different sowing dates on emergence of maize seedlings. The experiment consisted of two priming methods viz., i) Priming, ii) Non-priming, and ten sowing dates viz., i) 15 November, ii) 30 November, iii) 15 December iv) 30 December v) 14 January vi) 29 January vii) 13 February viii) 28 February, ix) 15 March, and x) 30 March. The experiment was laid out in a randomized complete block design with three replications. Results showed that germination percentage, germination index, mean germination time and dry matter/plant were influenced significantly by priming. The highest germination percentage, germination index, dry matter/plant and lowest mean germination time were recorded from primed seed sown in March followed by February and November sowings but those were very poor in December and January sowings. So, primed seeds should be sown in November and February for better stand establishment of maize. DOI: http://dx.doi.org/10.3329/bjar.v39i4.22549 Bangladesh J. Agril. Res. 39(4): 693-707, December 2014